Association of Single Nucleotide Polymorphism in Microrna146a And 196a2 Gene Towards Risk For Lung Cancer In Northindian Population - Sodhi, Kushaldeep Kaur (My University, 2014)
MicroRNAs (miRNAs) are small non-protein-coding RNAs that regulate the expression of corresponding messenger RNAs (mRNAs). Variations in the level of expression of distinct miRNAs have been observed in the genesis, progression and prognosis of multiple human malignancies. The present study was aimed to investigate the association between two highly studied miRNA polymorphisms (mir-146a rs2910164, mir-196a2 rs11614913) and cancer risk. A case-control study was performed on North Indian population. Odds ratio (OR) and 95% confidence interval (95% CI) were used to investigate the strength of the association. Participants who possessed heterozygous GC genotype and combined GC/CC genotypes for miRNA 146a gene showed high risk for LC especially for ADCC (OR=1.82, 95%C.I; 1.04- 3.20, p=0.03) when compared to wild type GG genotype. Significant association of GC genotype was more pronounced among light smokers (OR=1.86, 95%C.I; 0.90-3.82, p=0.002) indicating elevated risk of LC. On the other hand mutant (TT) genotype for miRNA 196a2 gene also showed high risk for LC (OR=3.51, 95%C.I; 1.36-9.04, p=0.009) especially SQCC (OR=4.98, 95%C.I; 1.55-15.9, p=0.006) and ADCC (OR=3.28, 95%C.I; 1.01-10.6, p=0.04). An interesting finding of this study was that non-smokers with mutant (TT) and combined CT/TT genotype were more susceptible for LC risk as compared to smokers. When analyzed in combinations of miR-146a and 196a2 polymorphism, combined heterozygous and mutant genotypes did show an association with overall LC and further these combinations had an elevated risk for ADCC and SCLC. The present study implicate the important role of mir-146a G>C and miR-196a2 C>T polymorphism with overall LC risk especially in North Indian population. Further studies with large sample size are needed to evaluate and confirm this association.
MT, DBTS
Keywords: lung cancer; miRNA; 196a2; 146